Post-pandemic comparative analysis between the health crisis and the public policies of the Playas Canton-Ecuador - Narváez Vásquez, Germán; Meza Clark, Teresa; Meza Clark, Jorge; González Garcilazo, Atzimba (Ingeniería Química y Desarrollo, 2024)
Faced with the crisis triggered by the SARS-CoV-2 pandemic, the global economy faced an unprecedented collapse, affecting both economic and social aspects. In Latin America and the Caribbean, fundamental sectors such as tourism suffered a significant paralysis. According to data from the World Tourism Organization (UNWTO), the influx of international tourists worldwide decreased drastically, suggesting a gradual reactivation of the sector. Ecuador, among the most affected countries, experienced an alarming increase in cases of contagion, ranking second in terms of mortality after Brazil. The objective of this research is to analyze the post-pandemic situation, comparing the health crisis with the public policies implemented in the Playas Canton, one of the main tourist destinations in the Province of Guayas. for which the following method was applied: i) Analysis of the socio-economic indicators applied to the national and international tourism sector, ii) Analysis of the case study and application of surveys to tourist centers in the Playas Canton in two moments, and iv) Inferences about affected indicators. The results obtained lead us to reflect on whether the bad situation that the Ecuadorian tourism sector is going through is the result of the pandemic or public policy.
Keywords: post pandemic; tourism sector; health crisis; public policy